PSBLAS a library for parallel linear algebra computation on sparse matrices. - Filippone, Salvatore (ACM transactions on mathematical software.)
Many computationally intensive problems in engineering and science give rise to the solution of large, sparse, linear systems of equations. Fast and efficient methods for their soltion are very important because these systems usually occur in the innermost loop of the computational scheme. Parallelization is often necessary to achieve an acceptable level of performance. This paper presents the design, implementation, and interface of a library of Basic Linear Algebra Subroutines for sparse matrices (PSBLAS) which is specifically tailored to distributed-memory computers. PSBLAS enables easy, efficient, and portable implementations of parallel iterative solvers for linear systems. The interface keeps in view a Single Program Multiple Data programming model on distributed-memory machines. However, the architecture of the library does not exclude an implementation in different paradigms, such as those based on the shared-memory model.